2022
DOI: 10.3390/nu14051026
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flavonoids Alleviate Inflammation and Vascular Endothelial Barrier Dysfunction Induced by Advanced Glycation End Products In Vitro

Abstract: The aim of this study was to compare the protective effects of three dietary flavonoids (apigenin-7-O-glucoside (A7G), isorhamnetin-3-O-rutinoside (I3R), and cyanidin-3-O-glucoside (C3G)) on advanced glycation end products (AGEs)-induced inflammation and vascular endothelial dysfunction. Furthermore, the potential mechanisms of varied effects of those three dietary flavonoids were analyzed by molecular docking analysis. Results showed that C3G (40 μM) achieved the best inhibition on inflammatory cytokines (TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The benefits of G. biloba and its preparations in the prevention and treatment of cardiovascular diseases mainly derive from the effective chemical components such as flavonoids and terpenoid lactones. In this study, through data mining and network pharmacology analysis of relevant literature, we found that the organic acid components (protocatechuic acid, caffeic acid, chlorogenic acid, and gallic acid), flavonoid components (quercetin‐3‐O‐glucoside, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, isorhamnetin‐3‐O‐glucoside, apigenin‐7‐O‐glucoside, and apigenin), and terpenoid lactones (bilobalide, ginkgolide A, ginkgolide B, ginkgolide C, and ginkgolide J) had different effects such as anti‐inflammatory and anti‐oxidative activities, protecting the nervous system, changing blood rheology, and so on 22–50 . These components may be the potential active substance basis of its anti‐IS effect, so they were included in the scope of analysis and investigation of the active components of GBE against IS.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The benefits of G. biloba and its preparations in the prevention and treatment of cardiovascular diseases mainly derive from the effective chemical components such as flavonoids and terpenoid lactones. In this study, through data mining and network pharmacology analysis of relevant literature, we found that the organic acid components (protocatechuic acid, caffeic acid, chlorogenic acid, and gallic acid), flavonoid components (quercetin‐3‐O‐glucoside, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, isorhamnetin‐3‐O‐glucoside, apigenin‐7‐O‐glucoside, and apigenin), and terpenoid lactones (bilobalide, ginkgolide A, ginkgolide B, ginkgolide C, and ginkgolide J) had different effects such as anti‐inflammatory and anti‐oxidative activities, protecting the nervous system, changing blood rheology, and so on 22–50 . These components may be the potential active substance basis of its anti‐IS effect, so they were included in the scope of analysis and investigation of the active components of GBE against IS.…”
Section: Discussionmentioning
confidence: 95%
“…Its anti-oxidative and anti-apoptotic effects are partly related to the activation of the PI3K-Akt signalling pathway. 47 In addition, GBE not only acts on the PI3K-Akt signalling pathway to exert a neuroprotective effect but also on the MAPK signalling pathway to improve IS. 80 Therefore, GBE exerts therapeutic effect on IS through multiple pathways and multiple targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AGEs were prepared by co-incubation of glucose and BSA, as described previously [ 78 ]. Briefly, BSA solution (50 mg/mL in PBS buffer) was incubated with or without D-glucose (0.5 M) for 90 days at 37 °C followed by dialyzing in PBS (pH 7.4, 5 mM) at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%